Corporate lawyers in the USA: pathway to gender parity?. Issue 2 (26th November 2020) - Ingersoll, Alicia R.; Glass, Christy; Cook, Alison
Abstract : Purpose: The current study aims to analyze the connection between gender disparities and employment in senior legal roles within large American firms. Specifically, this study seeks to uncover whether legal positions in large corporations reproduce inequalities in representation and wages, or whether these roles provide women with a pathway to greater gender parity. Design/methodology/approach: Investigating a large data set of over 2, 000 USA public companies over a ten-year period, this study examines the representation of women in senior legal roles, the likelihood of women's appointment to those roles as a function of the gender composition of the industry and if a wage gap exists between men and women serving in the top legal roles in corporate America. Findings: Findings suggest that rather than moving women closer to gender parity, in-house counsel positions reproduce many of the same inequalities found in large law firms, particularly with regard to representation in senior ranks and compensation. Originality/value: Research has illustrated that women experience disadvantage in terms of representation, wages and advancement in large law firms and in corporate executive suites. Women lawyers who occupy senior executive roles, however, may benefit relative to their non-legal counterparts given their education and expertise. Their credentials and relative status may contribute in reducing or eliminating gender disparities. This study extends current research by investigating this potential path to greater gender equality.